Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's solve the polynomial \( P(x) = 8x^3 + 4x^2 - 18x - 9 \) for \( x = -\frac{3}{2} \).
First, we break it down into parts and evaluate each term separately:
### Step 1: Evaluate \( 8x^3 \)
We need to calculate \( 8 \left( -\frac{3}{2} \right)^3 \):
[tex]\[ \left( -\frac{3}{2} \right)^3 = \left( -\frac{3}{2} \right) \times \left( -\frac{3}{2} \right) \times \left( -\frac{3}{2} \right) = -\frac{27}{8} \][/tex]
So,
[tex]\[ 8 \left( -\frac{3}{2} \right)^3 = 8 \times -\frac{27}{8} = -27 \][/tex]
Thus, the first term is \(-27\).
### Step 2: Evaluate \( 4x^2 \)
Next, calculate \( 4 \left( -\frac{3}{2} \right)^2 \):
[tex]\[ \left( -\frac{3}{2} \right)^2 = \left( -\frac{3}{2} \right) \times \left( -\frac{3}{2} \right) = \frac{9}{4} \][/tex]
So,
[tex]\[ 4 \left( -\frac{3}{2} \right)^2 = 4 \times \frac{9}{4} = 9 \][/tex]
Thus, the second term is \(9\).
### Step 3: Evaluate \( -18x \)
Next, calculate \( -18 \left( -\frac{3}{2} \right) \):
[tex]\[ -18 \left( -\frac{3}{2} \right) = 27 \][/tex]
Thus, the third term is \(27\).
### Step 4: Evaluate the constant term
The constant term does not change, it remains \(-9\).
### Step 5: Sum all terms
Finally, sum all the terms to get \( P\left( -\frac{3}{2} \right) \):
[tex]\[ -27 + 9 + 27 - 9 = 0 \][/tex]
### Conclusion
So, the value of the polynomial \( P\left( -\frac{3}{2} \right) \) is \(0\).
To summarize:
- The first term \( 8 \left( -\frac{3}{2} \right)^3 = -27 \)
- The second term \( 4 \left( -\frac{3}{2} \right)^2 = 9 \)
- The third term \( -18 \left( -\frac{3}{2} \right) = 27 \)
- The sum is \(-27 + 9 + 27 - 9 = 0\)
So, the final value of [tex]\( P\left( -\frac{3}{2} \right) \)[/tex] is [tex]\(0\)[/tex].
First, we break it down into parts and evaluate each term separately:
### Step 1: Evaluate \( 8x^3 \)
We need to calculate \( 8 \left( -\frac{3}{2} \right)^3 \):
[tex]\[ \left( -\frac{3}{2} \right)^3 = \left( -\frac{3}{2} \right) \times \left( -\frac{3}{2} \right) \times \left( -\frac{3}{2} \right) = -\frac{27}{8} \][/tex]
So,
[tex]\[ 8 \left( -\frac{3}{2} \right)^3 = 8 \times -\frac{27}{8} = -27 \][/tex]
Thus, the first term is \(-27\).
### Step 2: Evaluate \( 4x^2 \)
Next, calculate \( 4 \left( -\frac{3}{2} \right)^2 \):
[tex]\[ \left( -\frac{3}{2} \right)^2 = \left( -\frac{3}{2} \right) \times \left( -\frac{3}{2} \right) = \frac{9}{4} \][/tex]
So,
[tex]\[ 4 \left( -\frac{3}{2} \right)^2 = 4 \times \frac{9}{4} = 9 \][/tex]
Thus, the second term is \(9\).
### Step 3: Evaluate \( -18x \)
Next, calculate \( -18 \left( -\frac{3}{2} \right) \):
[tex]\[ -18 \left( -\frac{3}{2} \right) = 27 \][/tex]
Thus, the third term is \(27\).
### Step 4: Evaluate the constant term
The constant term does not change, it remains \(-9\).
### Step 5: Sum all terms
Finally, sum all the terms to get \( P\left( -\frac{3}{2} \right) \):
[tex]\[ -27 + 9 + 27 - 9 = 0 \][/tex]
### Conclusion
So, the value of the polynomial \( P\left( -\frac{3}{2} \right) \) is \(0\).
To summarize:
- The first term \( 8 \left( -\frac{3}{2} \right)^3 = -27 \)
- The second term \( 4 \left( -\frac{3}{2} \right)^2 = 9 \)
- The third term \( -18 \left( -\frac{3}{2} \right) = 27 \)
- The sum is \(-27 + 9 + 27 - 9 = 0\)
So, the final value of [tex]\( P\left( -\frac{3}{2} \right) \)[/tex] is [tex]\(0\)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.